(3bUI haGI SjOfG eYGP Hf LHd QVj Gddg Yfg hhaGI GdfHj Udi Gddg Ydjg hSdes - (3eLghds ((3YeQ GdTQHfGdjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYdejf Mci hGddg JYGdi CYde Cfg cGf QShd Gddg Udi Gddg Ydjg hSde LGdSG aj jhe ef GdCjGe HNjeJg EP ONd Ydjg YTQI ef CcGHQ Cgd Gdjefs
(3BNQgG (B:s
(3jG ef JLdi HceGd HgGFg aJMbbJ YXeI GdCSQGQ cja JNai hCfJ GdXGgQ Ce cja JZjH hCfJ GdQbjH GdMGVQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs